Dynamics and Impacts of the May 8th, 1902 Pyroclastic Current at Mount Pelée (Martinique): New Insights From Numerical Modeling - Gueugneau, Valentin; Kelfoun, Karim; Charbonnier, Sylvain; Germa, Aurelie; Carazzo, Guillaume (Frontiers in Earth Science, 2020)
The Mount Pelée May 8th, 1902 eruption is responsible for the deaths of more than 29,000 people, as well as the nearly-complete destruction of the city of Saint Pierre by a single pyroclastic current, and is, sadly, the deadliest eruption of the 20th century. Despite intensive field studies on the associated deposit, two conflicting interpretations of the pyroclastic current dynamics (either a blast or a simple ash-cloud surge) emerged in the 90’s and have been paralyzing research ever since, leaving numerous unknowns (i.e., source conditions, volume). This study is the first to investigate numerically the May 8th, 1902 pyroclastic current, using the new two-phase version of VolcFlow that simulates more accurately both parts of pyroclastic currents (i.e., the block-and-ash flow and the ash-cloud surge). Physical flow parameters are either extracted from field data or estimated empirically when no value was found in the literature. Among the two interpretations, only the simple ash-cloud surge is tested, generated from a block-and-ash flow initially supplied from the artificially recreated 1902 crater. The block-and-ash flow overflows from the southern V-shaped crater outlet and stays confined into the Rivière Blanche, whereas the ash-cloud surge expands radially and spreads westward, seaward, and eastward, ultimately reaching St Pierre 8 km away, within 330 s. The extent of both parts of the simulated current, as well as the thickness and the direction of the ash-cloud surge are accurately reproduced for a total volume of 32 × 106 m3, for which a significant part (one third) is deposited in the sea (not recorded in previous studies). Simulations demonstrate that the pear-like shape of the ash-cloud surge deposit is explained by a late surge production along the Rivière Blanche but also that a blast-like event may be required at the initial stage of the explosion, which in some way reconciles the two conflicting past interpretations. Results also highlight the role played by the topography in controlling transport and deposition mechanisms of such pyroclastic currents especially the lateral spreading of the ash-cloud surge. Our study improves the assessment of pyroclastic current-related hazards at Mount Pelée, which could be helpful for future eruptions.